Three new records of cheilanthoid ferns for Vietnam - Zhao, Junwen; Yang, Wenli; Wang, Caihong; Zhang, Gangmin (Phytotaxa, 2018)
Three new records of cheilanthoid ferns for Vietnam, i.e., Aleuritopteris sichouensis, A. formosana, and Cheilanthes fragilis are reported. Illustrations and notes on geographical distribution, habitat and taxonomy are also provided.